Analisis Kelengkapan Dan Pendokumentasian Rekam Medis Pasien Ketuban Pecah Dini (Kpd) Di Rumah Sakit Umum Daerah (Rsud) Kabupaten Sukoharjo Tahun 2015 - Beladina, Rizky Manda; , Sri Sugiarsi, SKM., M.Kes; , Yuli Kusumawati, SKM., M. Kes (Epid) (2016)
Medical record is a patient resume that must be complited from identification, authentication, important reports and documentation. based on preliminary survey results in a Regional General Hospital (RSUD) Sukoharjo there was incompletness in filling. The goal of this research was to analyze the completeness of medical record documents premature membranes rupture patients in RSUD Sukoharjo at 2015. This research was combination of quantitative and qualitative method (mixed methodology). The population of this research was medical record file of premature membranes rupture patients (PROM) in January-March 2015 and the sample were 36 patients medical records document. The results showed from 4 reviews completeness Document Medical Record (DRM) patients with premature rupture of membranes, incompleteness highest on the review of the completeness important report as many as 32 documents (88.89%) in the form sheet resume because doctor and midwifes did not record patient information back before going home for the sake of further examination.